2010
DOI: 10.3944/aott.2010.2109
|View full text |Cite
|
Sign up to set email alerts
|

Successful replantation in ten-digit amputation

Abstract: Amputations involving ten digits are very rare because of different lengths of the digits. A 34-year-old man working in a printing house presented one hour after guillotine amputation involving all ten digits. Surgery was initiated 80 minutes after admission and took seven hours. Under axillary anesthesia, the operation was performed by two teams each consisting of two microsurgeons and two assistants. Replantation was completed without the use of any skin graft or flap. Fingertip examination showed poor arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…There exist reports on patients who underwent successful replantation of amputated fingers, but few cases of multisegment amputation have been reported. 5 Belsky et al have reported successful treatment of a patient with a double level amputation through the palm and forearm. 3 Cai et al have described successful replantation of a multiple digit and circular palm amputation.…”
Section: Discussionmentioning
confidence: 99%
“…There exist reports on patients who underwent successful replantation of amputated fingers, but few cases of multisegment amputation have been reported. 5 Belsky et al have reported successful treatment of a patient with a double level amputation through the palm and forearm. 3 Cai et al have described successful replantation of a multiple digit and circular palm amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Although, some Asian studies have reported excellent results following replantation for zone 1 amputations, the technical and decision-making aspects of finger replantation are still being discussed 812. Bilateral multi-finger amputations are fortunately rare and only a few cases have been reported 1315…”
Section: Discussionmentioning
confidence: 99%